Two presidents are better than one : the case for a bipartisan executive branch - Orentlicher, David, 1955- (New York University Press, 2013)
When talking heads and political pundits make their "What's Wrong with America" lists, two concerns invariably rise to the top: the growing presidential abuse of power and the toxic political atmosphere in Washington. In this book, the author shows how the "imperial presidency" and partisan conflict are largely the result of a deeper problem - the Constitution's placement of a single president atop the executive branch. Accordingly, the author writes, we can fix our broken political system by replacing the one person, one-party presidency with a two-person, two-party executive branch. The author contends that our founding fathers did not anticipate the extent to which their checks and balances would fail to contain executive power and partisan discord. As the stakes in presidential elections have grown ever higher since the New Deal, battles to capture the White House have greatly exacerbated partisan differences. Had the framers been able to predict the future, the author argues, they would have been far less enamored with the idea of a single leader at the head of the executive branch and far more receptive to the alternative proposals for a plural executive that they rejected. Analyzing the histories of other countries with a plural executive branch and past examples of bipartisan cooperation within Congress, the author shows us why and how to implement a two-person, two-party presidency. Ultimately, this book demonstrates why we need constitutional reform to rebalance power between the executive and legislative branches and contain partisan conflict in Washington. -- Provided by publisher.